STUDI EKSPERIMENTAL PENGARUH KONFIGURASI SENGKANG PADA DAERAH TEKAN BALOK BETON SERAT BERTULANG - Sufaat, Muchtar; Pratama, Dian Adhitya; Purwanto, Purwanto; Sabdono, Parang (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
Concrete has relatively high compressive strength, in other hand higher concrete compression give more brittle of failure. There are several methods for improvement such as addition steel-fiber in concrete mix and confinement in the compression zone. This study present a further study on the influence of addition 0.5% steel-fiber of concrete volume to concrete mix and three specimen fiber concrete beams ware evaluated with three stirrup configuration (BF1, BF4, BF5) that concentrated in the compression zone. The study’s analyze using a pure beding test with 2 point load of a simply supported beam. The variation of stirrup configuration concentrated at pure beding moment zone of beam. The result of this study, the addition of steel-fibers to the concrete mix increased the cylinder compression strength by 11,96%, The moment capacity of BF4 increased by 0,96% compered to BF1 in other hand the specimen BF5 reduce by 4,1% compered to BF1 ,The Stiffnes of BF4 increased 132,64% and BF5 increased by 25,44% compared to BF1,The Ductility of specimen BF4 increased by 148,01% and BF5 increased by 3.97% compared to BF1.